O humor negro na Shoah : destinos para a mensagem sexual do outro no contexto de trauma social - Casemiro, Fúlvio César (2014)
This research examines the psychic functions of black humor produced by victims of the Shoah, a potentially traumatic social catastrophe, marked mainly by an excess of physical and psychic violence. We analyze the production of this type of humor from different contexts in which it figured, as the inside of Lager in European countries, and also by the following generations to Jewish survivors. We also approach the humor produced outside the Lager during the war although it is not considered for us as a black humor, but it preserves some similarities that subsidize our understanding about this subject. For this, we rely on studies of Freud on the subject in Psychoanalysis, and also we rely on the Theory of Seduction Generalized by Jean Laplanche (TSG). We believe that the black humor fulfill psychic functions already aired by Freud, as an attempt to be greater than the victimizer, to preserve the integrity of the ego narcissistic, and also as a unique way to extract pleasure from own pain. From the TSG we suggest that such activity is also a form of psychic translation for sexual messages implemented by the victimizer, as well as a possible way of linking and to became enigmatic for the messages by intrusion, which are marked by extreme violence. In our analyzes, we point out these functions occur interdependently in reports about black humor, and also how this activity is surrounded by paradoxes, like laughing from the pain itself, or be constituted as a psychic elaboration for some people and an act of aggression for others.